Mobile media distribution in developing contexts - Smith, Graeme (Department of Computer Science, 2014)
There are a growing number of mobile phones being used in developing contexts, such as Africa. A large percentage of these phones have the capability to take photographs and transmit them freely using Bluetooth. In order to provide people with media on their mobile phones public displays are becoming more common. Three problems with current public displays – cost, security and mobility – are discussed and system proposed that uses a mobile phone as a server.